2022
DOI: 10.5812/ijpr.123826
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EGFR Tyrosine Kinase: Design, Synthesis and Biological Evaluation of Novel Quinazolinone Derivatives

Abstract: : Impaired cell cycle regulation and disturbance in signal transduction pathway are two major causes of a condition defined as cancer, one of the significant reasons for mortality worldwide. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have been commonly used as anticancer agents, and the majority of this medications possess quinazoline moiety as a heteroaromatic core. In this study, two novel series of EGFR-TKIs containing quinazolinone core were designed and synthesized. Most compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that quinazolines could inhibit EGFR tyrosine kinase overexpression by restraining autophosphorylation in EGFR and EGF-stimulated signal transduction (22,23). Also, this scaffold shows antitumor activity by restraining the DNA repair enzyme system (23)(24)(25). As shown in Figure 1, there are some clinical medicines as antitumor agents with quinazoline or bioisosteres of the quinazoline ring, demonstrating the role of quinazoline in cancer therapy (23,26).…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have shown that quinazolines could inhibit EGFR tyrosine kinase overexpression by restraining autophosphorylation in EGFR and EGF-stimulated signal transduction (22,23). Also, this scaffold shows antitumor activity by restraining the DNA repair enzyme system (23)(24)(25). As shown in Figure 1, there are some clinical medicines as antitumor agents with quinazoline or bioisosteres of the quinazoline ring, demonstrating the role of quinazoline in cancer therapy (23,26).…”
Section: Introductionmentioning
confidence: 89%
“…MODEL online server (University of Basel, Basel, Switzerland) was utilized to estimate the 3D structure of the target protein by the application of the homology modeling method. The validation of the 3D protein structures was subsequently performed using the Ramachandran plot [5].…”
Section: Selection Of Ligands For Inhibitor Designmentioning
confidence: 99%
“…To conduct docking studies, it is necessary for the four potent medications to successfully pass a druglikeness test, which is employed to assess the suitability of a given chemical for usage as a pharmaceutical agent. The assessment of drug-likeness for all compounds was conducted utilizing the SwissADME drug discovery program [5]. The program in question is a rapid, precise, and user-friendly tool for predicting absorption, distribution, metabolism, and excretion processes.…”
Section: Drug-likeness Test -Swissadme Software Based On the Lipinski...mentioning
confidence: 99%
“…Therefore, this family which regulates tumor cell growth has been expansively investigated as a target for the inhibition of tumor growth (Assenat et al, 2015; Herbst, 2004). In view of the fact that, progress in the development of EGFR inhibitors is one of the most prominent topics of contemporary research in molecularly targeted therapy for the treatment of human cancer (Hynes & Lane, 2005; Nematpour et al, 2022; Tu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%